The Influence of Excitement and Sophistication on Brand Trust Through Brand Image as an Intervening Variable (Study on Shopee Users in Surabaya) - Ananda Leony; Rusdi Hidayat Nugroho (Universitas KH. Abdul Chalim Mojokerto, 2025)
Abstract